Stress recovery with social support: A dyadic stress and support task. (December 2022) - Løseth, Guro Engvig; Eikemo, Marie; Trøstheim, Martin; Meier, Isabell M.; Bjørnstad, Herman; Asratian, Anna; Pazmandi, Claudia; Tangen, Vegard Wathne; Heilig, Markus; Leknes, Siri
Abstract: How does social support bolster resilience? Here, we present a new dyadic paradigm to study causal mechanisms of acute and ecologically valid social support in the laboratory. The Dyadic Stress and Support Task (DSST) consists of a psychosocial stress phase and a recovery phase. During DSST stress, a pair of participants take turns to perform public speaking and mental arithmetic in front of a panel. Unable to see or touch each other, they witness each other's performance and feedback. During DSST recovery, the pair either interact freely with each other for 5 min (social support condition) or interact separately with an experimenter (non-support condition). To establish the validity of the DSST, we tested 21 pairs of long-term close friends in a pilot study. Primary outcome measures were ratings of affective state and bodily arousal (VAS scales 0–100). Secondary outcome measures were heart rate and salivary cortisol. DSST stress successfully induced subjective Stress Activation, increased Negative Affect and decreased Positive Affect. We also observed increased heart rate and salivary cortisol. After DSST recovery, Stress Activation and Negative Affect ratings were reduced in both groups. Positive Affect was completely restored to pre-stress baseline levels in the Social support group, while remaining significantly lower in the Non-support group. The DSST successfully induced stress and negative affect and captured stress recovery in both groups. Free-form interaction with the friend enhanced recovery of affective state, supporting the validity of spontaneous interaction between friends as a model of social support. Highlights: In this novel design, pairs of real-life friends undergo a dyadic social stress task, witnessing each other's performance. During recovery, participants interact freely (ecologically valid social support) or with an experimenter (non-support). The stress task increased heart rate, salivary cortisol, subjective stress and negative mood, and reduced positive mood. Social support greatly enhanced recovery of positive mood. All other stress responses recovered in both conditions.